To gaze upon wicked gods - Chang, Molly X. (To gaze upon wicked gods ;, 2024)
"Ruying, born with the power over death, must weigh if her family's life is worth betraying her country to strike a deal with an enemy prince. Heroes die, cowards live. Daughter of a conquered world, Ruying hates the invaders who descended from the heavens long before she was born and defeated the magic of her people with technologies unlike anything her world had ever seen. Blessed by Death, born with the ability to pull the life right out of mortal bodies, Ruying shouldn't have to fear these foreign invaders, but she does. Especially because she wants to keep herself and her family safe. When Ruying's Gift is discovered by an enemy prince, he offers her an impossible deal: If she becomes his private assassin and eliminates his political rivals--whose deaths he swears would be for the good of both their worlds and would protect her people from further brutalization--her family will never starve or suffer harm again. But to accept this bargain, she must use the powers she has always feared, powers that will shave years off her own existence.Can Ruying trust this prince, whose promises of a better world make her heart ache and whose smiles make her pulse beat faster? Are the evils of this agreement really in the service of a much greater good? Or will she betray her entire nation by protecting those she loves the most?"--